PRESSURE IN THE DAMPING DEVICE DURING PULSED LOADING - Smolyanitskij B.N.; Chervov V.V.; Vostrikov V.I. (My University, 2001)
In order to reduce forces in units subjected to shock loads, the damping devices absorbing the energy are applied. Characteristics of deformation wave propagation in the devices are considered. The wave is excited in compacted material as a results of impact of one metallic body with other metallic body. Solution of problem of absorbing the energy at test rig has been offered. Control of parameters of shock pulse acting on soil is provided. Laboratory test rig used in experiments has been described. Search of new damping material is discussed. New damping material should be found in order to reduce costs for performing the tests.